Modes of self-reflection in physical education instruction - Zhou, Tong; Bubnys, Remigijus; Grajauskas, Lauras; Cañabate, Dolors; Colomer, Jordi (Frontiers in Education, 2025)
PurposeSelf-reflection in physical education can effectively help teachers and students gain new insights and improve instruction. This study aims to conduct a specific analysis of research trends on self-reflection in physical education through scientometrics analysis, providing foundational material for teachers’ and students’ self-development.MethodsA scientometric analysis was conducted using WOS and Scopus databases. The search terms were “physical education” and “self-reflection” (2000–2024). From 207 initially retrieved articles, 46 were selected through systematic screening. The K value was 94%, with reliability (R) of 0.9987.Results(1) The overall trend from 2000 to 2024 shows an upward trajectory, divided into three stages: early stage (2000–2013) with slow development, middle stage (2014–2018) with gradual growth, and recent stage (2019–2024) with a significant increase in the amount of publications. This trend reflects the field’s evolution from initial limited attention to increasing scholarly focus in recent years, especially after 2019. Regarding literature types, qualitative research (n = 22, 48%) and quantitative research (n = 16, 35%) are equally emphasized. The research focus has shifted from reflective practices in physical education from teachers and coaches in the early years to increasing studies on students’ and athletes’ self-reflection in recent years, reflecting a transition from teacher-centered to learner-centered research perspectives. (2) The assessment effects of self-reflection in physical education are mainly reflected in three aspects: skill improvement, cognitive development, and emotional attitudes. Common assessment tools include questionnaires, reflection journals, interviews, and observations. (3) In using self-reflection, teachers and students emphasize their role in ongoing process within physical education instruction. Both teachers and students recognize the efforts in integrating reflection into daily teaching and learning. The content of reflection should be comprehensive, covering skills, cognition, and emotions. Reflection methods should be diverse, adapting to different learners’ needs and preferences. Finally, creating a supportive environment is crucial for promoting effective reflection with teachers fostering an open, trusting atmosphere that encourages students to express and share their progress in learning.ConclusionEffectively integrating self-reflection into physical education practice still faces challenges. Teachers and students need to adopt diverse reflection strategies and incorporate them into daily teaching and learning. Creating a comprehensiveness environment, cultivating reflection habits, and utilizing technology to aid reflection are directions that need attention in future practice.